Indole-Based Hydrazones Containing A Sulfonamide Moiety as Selective Inhibitors of Tumor-Associated Human Carbonic Anhydrase Isoforms IX and XII - Demir-Yazici, Kubra; BUA, Silvia; Akgunes, Nurgul Mutlu; Akdemir, ATİLLA; AKDEMİR, ATİLLA; Supuran, Claudiu T.; Guzel-Akdemir, Ozlen (My University, 2019)
Novel sulfonamidoindole-based hydrazones with a 2-(hydrazinocarbonyl)-3-phenyl-1Hindole-5-sulfonamide scaffold were synthesized and tested in enzyme inhibition assays against the tumor-associated carbonic anhydrase isoforms, hCA IX and XII, and the off-targets, hCA I and II. The compounds showed selectivity against hCA IX and XII over hCA I and II. Six compounds showed KI values lower than 10 nM against hCA IX or XII. Molecular modeling studies were performed to suggest binding interactions between the ligand and the hCA active sites.